THE STUDENTS’ DIFFICULTIES IN LEARNING READING COMPREHENSION USING COOPERATIVE LEARNING THROUGH JEOPARDY GAME - Susi Suryani; Evie Kareviati (IKIP Siliwangi, 2021)
English is an international language learned in Indonesia. One of the difficulties of student learning is when learning to read. They tend to read without knowing the meaning of the text they are reading. On this occasion the researcher tried to teach comprehension reading using cooperative learning through jeopardy games to increase students’ interest and ability in learning reading comprehension. In addition, researchers also want to find out what difficulties students face when learning to use jeopardy game through this jeopardy game. This research was conducted on students of class VIII E Semester 1 SMPN 1 Cililin which consists of 36 students. This research was conducted using the Classroom Action Research (CAR). From the results of the pretest and posttest, there were 20 pretest results from 36 students or 56% who succeeded in reaching the minimal completeness criteria. Whereas in the posttest there was an increase to 28 out of 36 students or 78,85% who successfully reached the minimal completeness criteria. Then it can be concluded the use of games in learning increases the ability of students in reading comprehension. However, there are some students who still find it difficult to learn to use this method because their vocabulary mastery is still lacking. Keywords: Reading Comprehension, Cooperative Learning, Jeopardy Game